Maintaining a High-Quality Screening Collection: The GSK Experience. (September 2021) - Gomez-Sanchez, Ruben; Besley, Stephen; Quayle, Julie; Green, Jasmine; Warren-Godkin, Natalie; Areri, Irene; Zeliku, Zoe
The storage of screening collections in DMSO is commonplace in the pharmaceutical industry. To ensure a high-quality screening collection, and hence effective and efficient high-throughput screening, all compounds entering the GlaxoSmithKline (GSK) screening collection undergo a liquid chromatography–mass spectrometry (LC-MS) quality control (QC). It is generally accepted that even under optimal conditions, a small percentage of these compounds are unstable after prolonged storage in DMSO. This article presents how these QC data can be mined using a data-driven clustering algorithm to identify chemical substructures likely to cause degradation in DMSO. This knowledge provides new structural filters for use in excluding compounds with these undesirable substructures from the collection. This information also suggests an efficient, targeted approach to compound collection clean-up initiatives. Stability studies are also designed to maintain a high-quality screening collection. To define the best practice for the storage and handling of solution samples, GSK has undertaken stability experiments for two decades, initially to support the implementation of new automated liquid stores and, subsequently, to enhance storage and use of compounds in solution through an understanding of compound degradation under storage and assay conditions.